THE ROLE OF STRATEGIC FORESIGHT IN IMPROVING SUPPLY CHAIN EFFICIENCY CASE STUDY IN THE INDUSTRIAL SECTOR (AL AIN MINERAL WATER COMPANY ( (World Economics and Finance Bulletin, 2026)
In light of the study's findings, it is clear that strategic foresight plays a pivotal role in improving supply chain efficiency within industrial companies. It contributes to enhancing the ability to predict future changes in the business environment, which positively impacts the accuracy of planning and decisionmaking. The results also showed that integrating strategic foresight tools with modern information systems leads to a higher level of responsiveness to market changes and reduces risks associated with uncertainty. Furthermore, it enhances the resilience of the supply chain and its ability to withstand crises and disruptions. In this context, the importance of building employees' analytical capabilities and developing their foresight skills emerged as a fundamental factor in achieving sustainable operational efficiency . Accordingly, the study emphasizes the need for Al Ain Mineral Water Company to adopt strategic foresight methodologies institutionally by integrating them into its strategic planning and supply chain management processes. It also recommends increasing investment in information systems and data analytics to support decision-making, along with establishing a specialized unit to monitor environmental changes and develop future scenarios. Furthermore, the study highlights the need to develop human resources through specialized training programs and to enhance collaboration with suppliers to achieve greater integration across the supply chain. Finally, adopting clear performance indicators to measure the impact of strategic foresight is a crucial step to ensure continuous improvement and achieve higher levels of efficiency and competitiveness in the industrial sector .
Keywords: Strategic foresight; supply chain; industrial sector Al Ain Mineral Water Company